Development of Dunkin' Pumpkins - a smart snack for kids - Savage, Sierra; Sparks, Halle; Steward, Megan; Manville, Erin; Getty, Kelly J.K. (My University, 2018)
School snack bars and vending machines must comply with regulations put into place by the U.S. Department of Agriculture’s Food and Nutrition Service (USDA/FNS). To be classified as a “smart snack,” the product must meet general nutritional regulations by containing 50% or more whole grains by weight, have the first ingredient as a fruit, vegetable, dairy product, or protein, or be a combination food with at least ¼ cup of fruit and/or vegetable. The objective of this study was to develop a “smart snack” geared towards kids and/or teens to be sold within schools. Dunkin’ Pumpkins was the product developed that consist of pumpkin whole grain oat cookies and a vanilla yogurt dip. The cookie contained 51% pumpkin and 39% whole grain oats. The product overall is 100 calories and each component meets the USDA/FNS standards for a “smart snack.” Xanthan gum was added to bind water and improve texture in the cookie, whereas gelatin was added to yogurt for thickening. To characterize Dunkin’ Pumpkins, size, color, texture, and water activity measurements were taken from three batches with three cookies per batch (n=9). The average cookie diameter and thickness was 41.8 ± 0.6 mm and 9.2 ± 0.3 mm. Color measurements for the cookie top averaged L* 44.1 ± 1.4, a* 14.5 ± 0.3, and b* 36.8 ± 2.3. The average peak positive force was 805.8 ± 56.7 g and positive area as 723.4 ± 83.2 g*sec. Water activity of the cookie was 0.96 ± 0.05 and 0.98 ± 0.03 for the yogurt dip. A sensory panel of children ≤ 16 years (n=20) and adults ≥ 18 years (n=20) was conducted. A hedonic scale of 1=dislike extremely to 9=like extremely was used to rate appearance, taste, texture, and overall acceptability of Dunkin’ Pumpkins when tasted as dipped into the yogurt. Children rated overall acceptability and taste as 7.3 ± 1.78 and 7.3 ± 1.71, whereas adults rated overall acceptability and taste as 6.2 ± 1.70 and 6.6 ± 1.61. Adult panelists stated they would purchase this product for $1-2 for their child at a school snack bar, but suggested the cookie could be sweeter and crispier. The amount of spices and honey could increase to yield a sweeter flavor in the cookies, however the total amount of calories may increase. Overall, this product was found to be appealing to children if additional modifications were tested to improve the overall taste and texture of the cookie.
Keywords: Spring 2018